COMPETENCIES IN EFFECTIVE LEARNING UNDER COVID-19 PANDEMIC - A CASE STUDY FOR COLLEGE FRESHMEN AT BINH DUONG UNIVERSITY - Quy, Vu Duc; Ngan, Duong Thi Thu; Mi, Nguyen Thi Tra; Van, Pham Cao; Binh, Tran Nguyen Thanh (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
The COVID-19 pandemic has profoundly affected every aspect of society, especially the education industry worldwide. Responding to the pandemic, Vietnamese universities have applied online classes via applications such as Google Meet, Microsoft Teams, Zoom. However, to improve the efficiency in the learning process, each student, especially college freshman, needs to equip themselves with the study skills under the impact of the COVID-19 pandemic. The authors surveyed the opinions of freshmen from Binh Duong University on online classes and learning competencies under the pandemic. Based on the results, the authors list the main difficulties in online learning of college freshmen and assess the importance of learning skills: Self-study skills, Choosing a study location and environment, Taking notes, Time Management and Teamwork. The article also presents some helpful learning methods and suggests their application to improve the efficiency of online learning